2022
DOI: 10.1093/applin/amac018
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Short-form Foreign Language Classroom Anxiety Scale

Abstract: Foreign language classroom anxiety (FLCA) is a popular construct in applied linguistics research, traditionally measured with the 33-item Foreign Language Classroom Anxiety Scale (FLCAS). However, recent studies have started utilizing the eight-item Short-Form FLCAS (S-FLCAS). There is therefore a need, which this study addressed in five sequential steps, to validate the S-FLCAS in order to ensure the validity and reliability of the scale. A sample of n = 370 foreign language learners was utilized in the valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 61 publications
8
34
0
Order By: Relevance
“…In particular, the negative emotion of FLA was strongly associated with Neuroticism (β = .551; p < .001), and it's second-order traits of general Anxiety (β = .185; p < .01) and Self-Consciousness (β = .183; p < .01). This finding is in line with previous research, as FLA has been found to be moderately positively associated with general anxiety as well as fear of negative evaluation (Botes, van der Westhuizen et al, 2022). Indeed, Horwitz et al (1986) conceptualised FLA from the 'buildings blocks' of communication apprehension, test anxiety, and fear of negative evaluation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, the negative emotion of FLA was strongly associated with Neuroticism (β = .551; p < .001), and it's second-order traits of general Anxiety (β = .185; p < .01) and Self-Consciousness (β = .183; p < .01). This finding is in line with previous research, as FLA has been found to be moderately positively associated with general anxiety as well as fear of negative evaluation (Botes, van der Westhuizen et al, 2022). Indeed, Horwitz et al (1986) conceptualised FLA from the 'buildings blocks' of communication apprehension, test anxiety, and fear of negative evaluation.…”
Section: Discussionsupporting
confidence: 91%
“…In turn, FLCA (F (6, 239) = 22.932; p < .001) was positively predicted by both Anxiety (β = .185, p < .01) and Self-Consciousness (β = .183, p < .01). It should also be noted that a considerable amount of the variance of FLA was explained by the subscales of Neuroticism (R 2 = .349), which given that FLA is associated with both a general level of anxiety as well as social anxiety (Botes, van der Westhuizen et al, 2022), is perhaps not a surprising result. Lastly, FLB was significantly predicted by the subscales of Neuroticism (F (6, 239) = 9.291; p < .001; R 2 = .189), however the standardised coefficient results were inconsistent in terms of slope.…”
Section: Neuroticismmentioning
confidence: 96%
“…The scale was more concise and remained highly reliable (Cronbach’s α = 0.89; McDonald’s ω = 0.89; n = 8) as the original one. The scale was recently validated by Botes et al (2022) . There were 8 items in the scale with a single dimension (e.g., “Even if I am well prepared for English class, I feel anxious about it.”), and two of the items were reversed (e.g., “I feel confident when I speak in English class.”).…”
Section: Methodsmentioning
confidence: 99%
“…It is thus suggested to adopt L2-specific measurements in future research to better capture the nature and complexities of L2 learning contexts. Recommended measures are the Foreign Language Classroom Anxiety Scale (FLCAS, Horwitz et al, 1986), the Short-form Foreign Language Classroom Anxiety Scale (S-FLCAS, Botes et al, 2022), the Boredom in Practical English Classes (BPELC, Pawlak et al, 2020c), and the Foreign Language Learning Boredom Scale (FLLBS, Li et al, 2021), all of which were originally developed and validated in the L2 learning contexts.…”
Section: Implications and Limitationsmentioning
confidence: 99%